A new species of Munidopsis Whiteaves, 1874 (Crustacea: Decapoda: Anomura) from the Northwest Indian Ocean Ridge - Dong, Dong; Li, Xinzheng; Zhou, Yadong; Wang, Chunsheng (Zootaxa, 2016)
A new species, Munidopsis militaris n. sp., from the Carlsberg Ridge, Northwest Indian Ocean Ridge is described herein. The species belongs to a group of species having a pair of epigastric spines, mesial and lateral eye-spines, abdominal tergites unarmed, five or six spines on the lateral margin of the carapace, and a denticulate carina on the distolateral margin of the P1 fixed finger. It can be distinguished from its relatives by the spinous lateral margin of the palm and dorsal carinae on the P2–4 propodus. The Munidopsis fauna of the Indian Ocean Ridge is seldom reported on; this new species is the sixth member of this genus found inhabiting the Indian Ocean Ridge.